2012
DOI: 10.1007/s00284-012-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antifungal Compounds Produced by Lactobacillus casei AST18

Abstract: Lactobacillus casei AST18 was screened as an antifungal lactic acid bacteria which we have reported before. In this research, the antifungal properties of cell-free culture filtrate (CCF) from L. casei AST18 were detected, and the antifungal compounds of CCF were prepared by ultrafiltration, and semi-preparative HPLC, and then determined by GC-MS. CCF was sensitive to pH and heat treatment but it was not affected by the treatment of trypsin and pepsin. Through the treatment of ultrafiltration and semi-preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…The interactions and mechanisms employed by C. albicans and Lactobacilli remain somewhat enigmatic. Lactobacilli species have demonstrated the ability to inhibit C. albicans growth via the release of hydrogen peroxide and fatty acids [88]. Previous to this, in an ex vivo experiment, L. rhamnosus and L. reuteri altered host responses by eliciting an increased inflammatory cytokine response in a C. albicans coinfection model [89].…”
Section: Denture Stomatitis: Mixing In a Rough Neighbourhoodmentioning
confidence: 99%
“…The interactions and mechanisms employed by C. albicans and Lactobacilli remain somewhat enigmatic. Lactobacilli species have demonstrated the ability to inhibit C. albicans growth via the release of hydrogen peroxide and fatty acids [88]. Previous to this, in an ex vivo experiment, L. rhamnosus and L. reuteri altered host responses by eliciting an increased inflammatory cytokine response in a C. albicans coinfection model [89].…”
Section: Denture Stomatitis: Mixing In a Rough Neighbourhoodmentioning
confidence: 99%
“…Prior to HPLC injection, extracts in methanol were filtered through a 0.2 lm PTFE Acrodisc CR syringe filter (Pall Corp., East Hills, NY). Gradient conditions were used with methanol/0.05% trifluoroacetic acid-solvent A (Sigma-Aldrich) and water/ 0.05% trifluoroacetic acid-solvent B at 1 ml/min and A/B ratios of 10:90, 100:0, and 100:0, with run time of 0, 30, and 33 min, respectively (Pryor et al 2006;Li et al 2012). Samples were eluted at a flow rate of 1 ml/min, and the elution profile was monitored with UV detector at 210 nm.…”
Section: Identification Of Antifungal Compoundsmentioning
confidence: 99%
“…Data (Figure 5 A) showed that the highest ( p <0.05) antibacterial activity was observed when pH was 5, excluding the effect of control. This indicated that either organic acids or other pH-dependent antibacterial compounds were responsible for the antibacterial effect [40]. These results indicated that P. orientale leaf extracts would be best used when pH was 5.…”
Section: Discussionmentioning
confidence: 87%